Modeling of Phase and Chemical Equilibrium on the Quaternary System Acetic Acid, n-Butanol, Water and n-ButylAcetate - Mandagaran, Beatriz Adriana (2009)
The correlation of the data for phase and chemical equilibrium in acetic acid-n-butanol-watern- butylacetate is presented. The azeotropic properties, the topological structure and the existence of a reactive azeotrope are discussed. The data are correlated by Hayden-O’Connell second virial coefficients and NRTL. Chemical equilibrium constant has a strong influence on the reactive azeotrope.